Common filaggrin null alleles are not associated with hymenoptera venom allergy in Europeans. - Aslam, A; Lloyd-Lavery, A; Warrell, D; Misbah, S; Ogg, G (2011)
The association of filaggrin mutations with atopic eczema (atopic dermatitis, AD) is well established and it is thought that filaggrin dysfunction impairs the skin's barrier function allowing allergen penetration and subsequent cutaneous sensitisation and inflammation. However, as most forms of barrier dysfunction are not associated with allergic sensitisation to common allergens, the possibility that filaggrin itself is involved in Th1/Th2 polarisation remains. We tested the hypothesis that allergen delivered to the skin independently of the stratum corneum is not associated with filaggrin mutations. Wasp stings bypass the stratum corneum and deliver antigen to the dermis. We found that European individuals with AD (n = 32) have an increased frequency of the 2 commonest filaggrin null mutations (R501X and 2282del4) compared to those with vespid allergy (n = 56) and healthy controls (n = 30). Thus, filaggrin does not appear to have a downstream effect on the development of allergic disease, and it is indeed filaggrin's role in the epithelial function that is likely to determine the link between filaggrin mutations and allergic sensitisation.